2020
DOI: 10.1093/gji/ggaa236
|View full text |Cite
|
Sign up to set email alerts
|

Upper crustal structure of NW Iran revealed by regional 3-D Pg velocity tomography

Abstract: SUMMARY We present the result of a 3-D Pg tomography in NW Iran to better understand the relationship between seismicity and velocity structure within the young continental collision system. In this regard, we have collected 559 07 Pg traveltime readings from 3963 well located earthquakes recorded by 353 seismic stations including 121 stations from four new temporary seismic networks. The most prominent feature of our Pg velocity model is a high correlation between the location of majority of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
3
12
0
Order By: Relevance
“…The thickness of overlying sediments ranges from 9 to 12 km at areas where high-velocity anomalies appear and exceeds 12 km at the surroundings. This range of sedimentary thickness is broadly consistent with that predicted from aeromagnetic data (7-16 km; Teknik & Ghods, 2017), Pg tomography (8-15 km; Maheri-Peyrov et al, 2020), and P-RF imaging (8-10 km; Motaghi et al, 2017).…”
Section: Decoupled Deformation Of the Zagros Sedimentary Coversupporting
confidence: 86%
See 1 more Smart Citation
“…The thickness of overlying sediments ranges from 9 to 12 km at areas where high-velocity anomalies appear and exceeds 12 km at the surroundings. This range of sedimentary thickness is broadly consistent with that predicted from aeromagnetic data (7-16 km; Teknik & Ghods, 2017), Pg tomography (8-15 km; Maheri-Peyrov et al, 2020), and P-RF imaging (8-10 km; Motaghi et al, 2017).…”
Section: Decoupled Deformation Of the Zagros Sedimentary Coversupporting
confidence: 86%
“…Active‐source methods, despite having impressive resolution, are challenging for region‐scale imaging due to their enormous cost. Passive‐source methods based on either body wave travel time or surface wave dispersion data require a uniform and dense distribution of stations and/or events, and suffer from a low spatial resolution due to strong along‐ray averaging effects (e.g., Maheri‐Peyrov et al., 2020). The P‐wave receiver function (P‐RF), because of its excellent resolution in both horizontal and vertical directions, has been used routinely to constrain crustal structures beneath single stations or dense arrays.…”
Section: Introductionmentioning
confidence: 99%
“…NW Iran is a region of anomalously warm crust and upper mantle and the Sahand and Sabalan have had post-collisional magmatic activities as recently as Pliocene-Quaternary (Chiü et al 2013). The regional Pg-wave tomography of Maheri-Peyrov et al (2020) and the P-wave tomography of Bavali et al (2016) revealed low-velocity zones at mid-crustal to subcrustal mantle depths directly beneath the volcanoes, which could be related to their thermal source regions. This structural setting can create a layered anisotropy at a local scale and explain the smaller delay times in the regions of the two volcanoes.…”
Section: Discussion Comparison Between Sk(k)s and S Wave Splitting Parametersmentioning
confidence: 96%
“…Maheri-Peyrov et al, 2018) also show slow Pg velocity (i.e., not in the range of velocity of upper crustal crystalline rocks) of the upper crust within the region around Kermanshah ophiolites. This indirectly implies that the high P velocity ophiolitic rocks are too thin to increase the average velocity of the sedimentary cover.…”
mentioning
confidence: 94%